Layered double hydroxides: Structures, properties and applications - Lei, L; Zhang, W; Hu, M; O'Hare, D (2005)
This paper reviews chemistry and applications of layered double hydroxides (short as LDHs). The LDHs have chemically bonded, therefore pretty rigid hydroxide layers and interlayer anions; and they outstand there because of their marvelous reversible anion-exchange capabilities and thermochemical behaviors. Recently, another aspect has attracted much attention that they constrain the interlayer anions and make them react in special ways, consequently produce selective products. Benefiting from the above three properties of LDHs, researchers have investigated their applications in preparations of various materials (including organic-inorganic composites), anionic exchange and removals of hazardous anions, chemical separations of organic geometric isomers, controls of chemical reactions, storage and control release of biomolecules, preparation of flame retarding materials/additives, catalysts and catalyst supports, and topochemical syntheses.